2013
DOI: 10.4141/cjas2012-095
|View full text |Cite
|
Sign up to set email alerts
|

Replacing canola meal as the major protein source with wheat dried distillers’ grains alters omasal fatty acid flow and milk fatty acid composition in dairy cows

Abstract: , T. 2013. Replacing canola meal as the major protein source with wheat dried distillers' grains alters omasal fatty acid flow and milk fatty acid composition in dairy cows. Can. J. Anim. Sci. 93: 137Á147. Wheat dried distillers' grains with solubles (W-DDGS) has a high fat content and is now commonly fed to dairy cows in western Canada. The objective was to determine the effects of replacing canola meal (CM) with W-DDGS on omasal fatty acid (FA) flow and milk FA composition. Four ruminally-cannulated lactatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The present study found reduced SFA in milk by feeding WDG, which is similar to a previous study containing increasing amounts of WDG in the concentrate mix (60 and 120 g kg −1 on DM basis) of lactating ewes 38 . However, several studies found no significant differences in the SFA concentrations in milk from 60 up to 200 g kg −1 DM inclusion levels of WDG 39,40 . The reduction of SFA was reported to be due to either a higher secretion of long‐chain FA from the blood and/or a lower de novo synthesis of FA in the mammary gland 38 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present study found reduced SFA in milk by feeding WDG, which is similar to a previous study containing increasing amounts of WDG in the concentrate mix (60 and 120 g kg −1 on DM basis) of lactating ewes 38 . However, several studies found no significant differences in the SFA concentrations in milk from 60 up to 200 g kg −1 DM inclusion levels of WDG 39,40 . The reduction of SFA was reported to be due to either a higher secretion of long‐chain FA from the blood and/or a lower de novo synthesis of FA in the mammary gland 38 .…”
Section: Discussionsupporting
confidence: 89%
“…46 The increased milk concentrations of key FA such as LA, ALA and RA were also found in previous studies when feeding cows WDG, instead of barley silage or corn grain and soybean meal or canola meal. [38][39][40] In the present study, dietary LA intake was higher when WDG was fed (which may explain the increase in milk LA concentrations), while the transfer rates from feed to milk were lower, thus indicating extensive biohydrogenation, which may have increased the synthesis of VA in the rumen and RA in the mammary gland 34,46 and explain their higher concentrations in milk. Despite the higher feed-to-milk transfer rate of LA in cows fed RSM, milk from RSM cows had lower concentrations in LA, indicating that the higher intakes of LA when cows fed WDG (+44%; +30 g d −1 ) were enough to increase milk LA concentrations but also provide adequate substrate for the higher synthesis of VA and RA (which originate from dietary LA and ALA 34,46 ).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…It could be used as a substitute to barley (up to 15%), as demonstrated by Damiran and McKinnon [175], but they found no significant change in the performance of steers. Besides, the milk yield was significantly increased in cattle supplemented with rapeseed meal (compared to those fed with soybean meal) [176,177], and in a combination of rapeseed meal with wheat distillers' dried grains with soluble [178], or as a substitution for wheat [179]. Incorporating rapeseed meals in pig diet was limited to 25% [180] since they only could tolerate 2 to 2.5 µmol/g of glucosinolates [151,181].…”
Section: Animal Foddermentioning
confidence: 99%
“…Nonetheless, it is likely that fat remaining after centrifugation is tightly adhered to the feed particles and as a result less likely to undergo BH in the rumen. In a recent attempt to study the flow of FA in cattle consuming wheat DG, Chibisa et al (2013) added wheat DG to the ration by replacing canola meal at 10, 15, and 20% of the diet DM. In these diets the concentration of C18:2, C18:1, and C16:0 increase with increasing levels of wheat DG.…”
Section: Milk Fatmentioning
confidence: 99%